PENERIMAAN PAJAK PERTAMBAHAN NILAI DIDETERMINASI OLEH JUMLAH PENGUSAHA KENA PAJAK DAN PENAGIHAN PAJAK (Studi Kasus Pada Kantor Pelayanan Pajak Pratama Majalaya Tahun 2010-2014) - Ritonga, Jayanthi Oktavia (Jurnal Riset Akuntansi, 2017)
The phenomenon that occurs in this study for the years 2011-2014 there was an increasein the Number of taxable Employers KPP Pratama Majalaya but development value added taxreceipts that is produced is decreased. The next phenomenon that occurs in 2011-2012 wherean increase in tax collection.The purpose of this study was to determine how much influence the Number of taxableEmployers on development value added tax receipts, and tax collection on development valueadded tax receipts. This study in Kantor Pelayanan Pajak (KPP) Pratama Majalaya 2010-2014.The method used is linear regression, Researchers also tested whether there aredeviations from the assumption of normality test, autocorrelation, multicollinearity, andheteroscedasticity.The results showed that there is a effect partially between the number oftaxable Employers on the value added tax receipts. And there is a effect between on tax collectionwith forced letter on the value added tax receipts.